A study of prevalence and factors associated with Caesarean hysterectomy in hospital universiti sains malaysia - Yusmadi, Abdullah (2007)
Obstetric hysterectomy is done to safe patient's life in case of uncontrolled bleeding during caesarean section. It is also done as elective for case of cervical cancer. Caesarean hysterectomy was defined as one performed for the haemorrhage unresponsive to other treatment following caesarean section including for uterine rupture. Wan Abu Bakar (1993) showed the percentage of caesarean hysterectomy was 0.3% (1 : 1926 total of delivery). During that study period, 24 cases of caesarean hysterectomy was reported in which 18 patients had underwent total hysterectomy and 6 patients underwent total hysterectomy. The study also showed the major indication for the operation was uterine atony. Objectives: To determine the prevalence and the associated factors for caesarean hysterectomy. The complications of the operation also were identified. Methodology : This study was conducted at Hospital Universiti Sains Malaysia from January 1996 till December 2005. All patients who underwent caesarean hysterectomy in the study period were included in the sample size, included patients with uterine rupture. The patient who underwent postpartum hysterectomy were also recorded as to compare with caesarean hysterectomy. Patient's information were obtained from the record office. The pennission was obtained from Pengarah Hospital Universiti Sains Malaysia. The study was ethically approved from the HUSM ethical committee (Number 170.4(5». Results : There were 65 cases of caesarean hysterectomy was done through out the study period where the total nwnber of deliveries were 70 842 deliveries. Therefore the caesarean hysterectomy rate is 0.9: 1000. Most frequent indications were placenta accreta (46.2 % , 30 out of 65), uterine atony (33.8 %, 22 out of 65), uterine rupture (16.9 % , 11 out of 65) , carcinoma of cervix (I.S % ,lout of 65). From this study 44.6% (29 out of 65) had history of previous caesarean section and 33.8% (22 out of65) had undergone uterine curettage. The number of caesarean deliveries and ERPOC were increasing trend and increased the risk of placenta aecreta proportionally. Fifty three (81.5%) of the hysterectomy cases were total hysterectomy and twelve (18.5 %) of the cases were subtotal hysterectomy. In this study, 18.5% (12 out of 65) of the patients complicated by coagulopathy and 16.9% (11 out of 65) had febrile illness. 9.2% (6 out of 65) had bladder injury and one patient developed complicated by amniotic fluid embolism. xv